Modelling to determine optimal-water availability scenarios under drought conditions in agricultural environments: A study of the Western Cape, South Afica - Ngwenya, Mthulisi (University of the Witwatersrand, Johannesburg, 2024)
Prolonged drought events have created persistent water shortages, and this has led to fierce competition amongst water users and a decline in agricultural production in agroecological zones (AEZs) of the Western Cape (WC) Province in South Africa. A common strategy to manage drought and the associated water shortages is based on crisis management (ex−ante). However, a risk-based approach seems to be in line with proactive and optimal water resources management. Therefore, considering the challenges and opportunities in the context of sub-Saharan Africa's policies and frameworks, how can drought risk management be most effectively and sustainably implemented the through monitoring and vulnerability risk assessment considering the case study of the agricultural environments in semi-arid areas. In this regard, the overarching aim of this study was to quantify and analyse the impacts of meteorological drought on sustainable water availability in the AEZs of the WC during the between from 1980 and 2050. This study used two forms of datasets: observational data and model simulations. Observed precipitation data (1980–2020) were gathered from the University of East Anglia’s Climate Research Unit gridded Time Series (CRU TS Version 4.07) https://www.cru.uea.ac.uk/cru/data/hrg database using Google Earth engine interface, while future precipitation datasets (2021–2050) under SSP5–8.5, SSP2–4.5 and SSP1–2.6 climate scenarios were generated by the sixth version of Model for Interdisciplinary Research on Climate, (MIROC6) https://esgf–node.llnl.gov/search/cmip6/ database. These datasets were processed using the Standardized Precipitation Index (SPI), Reliance (Rel), Resilience (Res) and Vulnerability (Vul) indicators and Sustainability Index (SI). The Mann-Kendall (M-K) test was used for trend analysis at a significance level of p < 0.05. The results revealed that under the influence of climate change there will be a decrease in expected precipitation between 2021 and 2050 across all districts, with the greatest decrease expected in sub-tropical cool sub humid zone (STCSH). The average Rel index across the study area in observed data was calculated to be 0.53, which changed to 0.49 in the SSP2−4.5 scenario, a decrease of 1.43%. There was no change in average Res index across the study area for both base period and under climate change scenario, calculated to be 0.42. The average Vul index across the study area in the base period was calculated to be 0.47, which changed to 0.51 under the influence of climate change, an increase of 7.08%. The study findings indicated a progressive reduction in water availability across climate change scenarios with SSP5–8.5 indicating statistically significant negative trends while both the SSP2–4.5 and SSP1–2.6 indicated mostly positive insignificant precipitation trends in the near term (2021–2050). The results further indicate that in arid climates, future SI, exhibited moderate water shortage (0.60< SI <0.80), while in semiarid climates future SI values, exhibited mild water shortages (0.62< SI <0.71); while in the humid climates future SI values projected normal to above normal water availability condition (0.52 < SI <0.58). Trend analysis results indicated non-insignificant positive vulnerability trends and significant negative trends for both reliability and resilience indicator. Overall, the results suggest that between 2021 and 2050 drought conditions will aggravate water scarcity in AEZs compared to observed drought condition (1980-2020). The results of this study can aid policymakers in mitigating drought related water scarcity and foster drought resilient communities.
Thesis Submitted in fulfilment of the requirements for the Degree of Doctor of Philosophy, to the Faculty of Science, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2024.
Keywords: Drought; Climate change; Water availability; Climate models; Reliance; Vulnerability; Resilience; UCTD; SDG-6: Clean water and sanitation; SDG-13: Climate action